Three dimensional kinematic differences between male and female soccer players - Loud, D.; Grimshaw, P.; Kelso, R. (ISBS Proceedings Archive (Michigan), 2021)
This research describes a method of biomechanical analysis that allows for kinematic data to be captured in a game-like environment and key biomechanical differences between male and female soccer players to be identified. Male (n=3) players aged between 22 and 24 years and female players (n=3) aged between 19 and 23 years were recorded using a VICON motion capture system operating outdoors at an artificial grass venue. Biomechanical measurements of the lower limb such as inversion/eversion and flexion/extension of the ankle; the flexion/extension, varus/valgus and internal/external rotation of the knee; and the internal/external rotation and abduction/adduction of the hip, were recorded. Initial observations showed an increase in knee valgus and external tibial rotation in female players` key activities performed during a soccer game.